Exploitation of Man by Man in Charles Dickens’ A Christmas Carol - TIFANI DEWI (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2019)
Exploitation of man by man is the main focus of this study in the Charles Dickens novel titled A Christmas Carol. This study uses descriptive analysis. The main data is taken from Charles Dickens novel A Christmas Carol. This thesis aims to analyze how Scrroge exploits Bobs description, as well as analyze the factors that make Scrooge exploit Bob. Exploitation of man by man is a form of exploitation that involves two relata in which the rich aim to take advantage of the object. The concept of exploitation of man by man refers to the A as the rich who has the power to take advantage of B which is poor and powerless. This thesis uses the exploitation of man by man theory by Nicholas Vrousalis. This theory is well applied to reveal existing problems. The analysis also shows that Scrooge has been described as an exploitative image that dominates this novel. Scrooge with his power, dominates and exploits Bob by treating him unfairly on the counting house, such as giving underpaid and giving work time beyond normal limits. This is because Scrooge feels that he has more authority than Bob. This made Bob and his family increasingly poor, which in the beginning they were poor and vulnerable. However, exploitation must lead to something that is not fair. Supervision and control may avoid these actions. Exploitasi Manusia dengan Manusia adalah fokus utama penelitian ini dalam novel Charles Dickens berjudul A Christmas Carol. Penelitian ini menggunakan analisis deskriptif. Data utama diambil dari novel Charles Dickens, A Christmas Carol. Tesis ini bertujuan untuk menganalisis bagaimana Scrroge mengeksploitasi deskripsi Bob, serta menganalisis faktor-faktor yang membuat Scrooge mengeksploitasi Bob. Eksploitasi manusia oleh manusia adalah bentuk eksploitasi yang melibatkan dua relata di mana orang kaya bertujuan untuk mengambil keuntungan dari objek tersebut. Konsep eksploitasi manusia oleh manusia mengacu pada A sebagai orang kaya yang memiliki kekuatan untuk mengambil keuntungan dari B yang miskin dan tak berdaya. Tesis ini menggunakan eksploitasi teori manusia oleh manusia oleh Nicholas Vrousalis. Teori ini diterapkan dengan baik untuk mengungkapkan masalah yang ada. Analisis juga menunjukkan bahwa Scrooge telah digambarkan sebagai gambar eksploitatif yang mendominasi novel ini. Scrooge dengan kekuatannya, mendominasi dan mengeksploitasi Bob dengan memperlakukannya secara tidak adil di rumah hitung, seperti memberi gaji rendah dan memberikan waktu kerja di luar batas normal. Ini karena Scrooge merasa bahwa dia memiliki otoritas lebih dari Bob. Ini membuat Bob dan keluarganya semakin miskin, yang pada awalnya mereka miskin dan rentan. Namun, eksploitasi harus mengarah pada sesuatu yang tidak adil. Pengawasan dan kontrol dapat menghindari tindakan ini.